(untitled) (Revista Direito em Debate, 2021)
The original acquisition of property and the real rights inherent to it through usucaption is one of the most relevant legal figures in our country order. Until the advent of the Code of Civil Procedure of 2015, the procedure that declared the property based on usucaption was done almost exclusively before the Judiciary. With the new procedural law, which modified the Public Registers Law, it was allowed this procedure to be done before the Registry of Real Estate in the county in which the property was located. The present article intends to analyze if there was actually an extrajudicial procedure with effective practical utility, aiming at the conclusion that, despite being foreseen in 2015, this reduce of judicial involvement in usucaption only became effective with the entry into force of Law No 13.465 of 2017, due to the modification of certain procedural rules that will be duly detailed in this study.